Serious Games in Cultural Heritage: A Review of Practices and Considerations in the Design of Location-Based Games - Boaventura DaCosta; Carolyn Kinsell (MDPI AG, 2022)
The overwhelming growth and popularity of mobile devices and games have motivated initiatives to explore mobile and augmented reality to bring the physical and virtual together. While several domains have been the recipient of such focus, particular importance has been placed on the cultural heritage (CH) field, with examples demonstrating the promise of location-based games (LBGs) at enhancing the CH experience aimed at promoting awareness. Games like Pokémon GO have exacerbated the appeal of LBGs, showing that they can be as popular as blockbuster video games. However, as much potential as LBGs have in raising CH awareness, they can be challenging to build because, unlike their commercial counterparts, their primary aim is learning, emphasizing the cultural significance of the real-world location rather than augmented assets. With limited research that explicitly identifies elements in creating these games in CH contexts, this work aimed to identify design practices and considerations in the design of LBGs. This work is intended for educators, researchers, instructional designers, game developers, and those in the CH field interested in exploring creative ways to embody a deeper understanding of and appreciation for CH.